Determinación del costo de producción en el cultivo de arroz en la propiedad del señor Jesús Armando Alvarracín Cordero del cantón El Triunfo, periodo: enero a mayo 2013 - Carcelén Ruíz, Angélica Anabel (2015)
The present so-called research thesis: "determination of the cost of production in the CULTIVATION of rice in the property of the LORD JESUS ARMANDO ALVARRACIN Lamb of the CANTON: the triumph, period: January to may 2013", was developed with the aim of determining the cost of production of 20 hectares of rice, which necessitated the application of agricultural accounting in this business whose commercial activity lacks a proper accounting system and where control of production costs such as raw material, labor and overhead costs be carried efficiently, whereas the accounting principles generally accepted. The same occurs to meet the owner of this production unit the result obtained through the determination of the total cost of the production of the grass. It is worth mentioning that this work was prepared according to the rules of academic regime of the National University of Loja, career of accounting and auditing. The goals set in the business of Mr Alvarracín, arrived to meet successfully, the application of agricultural accounting allowed to determine the cost of raw materials, labor and general production costs; also by the structure of the Plan and Manual of accounts; the lifting of the inventory of assets, rights and obligations met heritage invested in this business and developed the newspaper book which allowed registration of the transactions related to the economic activity and next internal documents used in this type of accounting was determined the cost of rice production which will allow its owner to make the right decisions when the case warrants it; Therefore it is recommended to continue applying the agricultural accounting.